Artificial Intelligence and Cloud-Based Accounting Information Systems: Enhancing Financial Reporting Reliability and Cybersecurity in the Digital Era - Aisyah, Putri Nur; DP, Rina Tjandrakirana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine how the integration of Artificial Intelligence (AI) and Cloud-Based Accounting Information Systems (CAIS) enhances the reliability of financial reporting and strengthens cybersecurity. Using a qualitative Systematic Literature Review (SLR) and guided by Sociotechnical Systems Theory, the research synthesizes 28 academic sources. Results show that AI and CAIS improve accuracy, fraud detection, and real-time reporting while mitigating cyber threats through encryption and automated monitoring. However, challenges include algorithmic bias, regulatory complexity, and organizational misalignment. The study concludes that joint optimization of technical and social systems is essential for achieving secure, transparent, and resilient digital financial reporting environments.